2006
DOI: 10.2331/suisan.72.34
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of ayu spermatozoa

Abstract: Semen of ayu Plecoglossus altiveris altiveris cryopreserved with a diluent comprising 10 MeOH(cryoprotectant) and 90 fetal bovine serum (FBS: extender) showed a higher rate of motility than that cryopreserved with other cryoprotectants (DMSO, glycerol, N,N dimethylacetamide, N,N dimethylformamide, ethanol) and extenders (ayu serum, artiˆcial seminal plasma, 300 mM or 600 mM glucose).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…It is well known that MeOH is less toxic and that its high permeability provides good survivability with spermatozoa in many teleost species (Harvey, 1983;Leung, 1987;Rana & McAndrew, 1989;Lahnsteiner et al, 1997). Several studies have shown FBS to be an excellent cryopreservation diluent (Aoki et al, 1997;Ohta et al, 2001;Tsutaka et al, 2006). In the present study, no conspicuous differences in post-thaw motility were found between ASP and FBS when 10% MeOH was used as a cryoprotectant.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…It is well known that MeOH is less toxic and that its high permeability provides good survivability with spermatozoa in many teleost species (Harvey, 1983;Leung, 1987;Rana & McAndrew, 1989;Lahnsteiner et al, 1997). Several studies have shown FBS to be an excellent cryopreservation diluent (Aoki et al, 1997;Ohta et al, 2001;Tsutaka et al, 2006). In the present study, no conspicuous differences in post-thaw motility were found between ASP and FBS when 10% MeOH was used as a cryoprotectant.…”
Section: Discussioncontrasting
confidence: 39%
“…Several studies have shown FBS to be an excellent cryopreservation diluent (Aoki et al , 1997; Ohta et al , 2001; Tsutaka et al , 2006). In the present study, no conspicuous differences in post‐thaw motility were found between ASP and FBS when 10% MeOH was used as a cryoprotectant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low osmotic pressure of FBS might be unsuitable for sea cucumber sperm. In fish sperm cryopreservation, FBS is reported to be an effective extender for the cryoprotectant (Aoki, Okamoto, Tatsumi, & Ishikawa, ; Ohta, Kawamura, Unuma, & Takegoshi, ; Tsutaka et al, ). In the present study, when FBS was added to seawater at a ratio of 20%, a significantly higher post‐thaw motility was obtained than with ASW alone.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation was conducted as described previously (Tsutaka, Yamamoto, Naka, Shimizu, Nakamura, Takii & Ohta 2006). Milt was diluted 1:49 with a cryopreservation extender comprising 10% methanol and 90% foetal bovine serum (F6178, Sigma‐Aldrich Japan, Tokyo, Japan) at room temperature (∼20 °C), and the mixture was dispensed into 150 μL acrylic capillary tubes (110 mm in length, 2 mm in diameter; Hematlon ‐ l ; Hayashi Science, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%